2018
DOI: 10.1371/journal.pone.0201247
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of newly detected diabetes in pregnancy in Qatar, using universal screening

Abstract: BackgroundDiabetes first detected during pregnancy is currently divided into gestational diabetes mellitus (GDM) and diabetes mellitus (DM)- most of which are type 2 DM (T2DM). This study aims to define the prevalence and outcomes of diabetes first detected in pregnancy based on 75-gram oral glucose tolerance test (OGTT)using the recent WHO/IADPSG guidelines in a high-risk population.MethodsThis is a retrospective study that included all patients who underwent a 75 g (OGTT) between Jan 2016 and Apr 2016 and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
5
27
1
Order By: Relevance
“…In the Middle East region, many studies have assessed the incidence of GDM with the application of the new diagnostic cut-off values, but without comparison to the previous cut-off values. The incidence of GDM in the present study is comparable to the reported incidence in Saudi Arabia, 21 which is 51%, but it is lower than the rates reported from Jordan 9 (13.5%) and Qatar 20 (24.0%). The wide variation in these estimates may be attributed to the study design differences and in selecting the study subjects and ethnic and sociocultural factors.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the Middle East region, many studies have assessed the incidence of GDM with the application of the new diagnostic cut-off values, but without comparison to the previous cut-off values. The incidence of GDM in the present study is comparable to the reported incidence in Saudi Arabia, 21 which is 51%, but it is lower than the rates reported from Jordan 9 (13.5%) and Qatar 20 (24.0%). The wide variation in these estimates may be attributed to the study design differences and in selecting the study subjects and ethnic and sociocultural factors.…”
Section: Discussionsupporting
confidence: 70%
“… 18 , 19 On applying the IADPSG criteria, the prevalence of GDM in Qatar, UAE, and Saudi Arabia was found to be 24.0%, 37.7%, and 51%, respectively. 20 , 21 These figures are predicted to increase further in this region due to the sedentary lifestyle and change in dietary habits resulting in a growing obesity epidemic. Subsequently, it is anticipated that there will be a considerable rise in T2DM and perhaps GDM.…”
Section: Introductionmentioning
confidence: 99%
“…The highest prevalence was obtained by the IADPSG method, which was similar to a review study carried out in India [21]. This could be due to the low threshold for fasting blood glucose in this method, which is at a low level; although IADPSG has gained popularity in recent years considering its lower costs and better responses and improvements in pregnancy outcomes in mothers [22,23].…”
Section: Discussionsupporting
confidence: 64%
“…,43-50, 56, 57, 62-72, 79, 80, 82-98, 105-112], followed by eight (9.9%) in Kuwait[20,21,24,41,51,73,81,99], seven (8.6%) in each of Qatar[42,52,53,60,61,74,113] and the UAE[58, 59, 75-77, 100, 101], six (7.4%) in Oman…”
mentioning
confidence: 99%